2016
DOI: 10.1093/mnras/stw1891
|View full text |Cite
|
Sign up to set email alerts
|

The SAMI Galaxy Survey: the link between angular momentum and optical morphology

Abstract: We investigate the relationship between stellar and gas specific angular momentum j, stellar mass M * and optical morphology for a sample of 488 galaxies extracted from the SAMI Galaxy Survey. We find that j, measured within one effective radius, monotonically increases with M * and that, for M * >10 9.5 M , the scatter in this relation strongly correlates with optical morphology (i.e., visual classification and Sérsic index). These findings confirm that massive galaxies of all types lie on a plane relating ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
123
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(139 citation statements)
references
References 110 publications
16
123
0
Order By: Relevance
“…To estimate j * , they used star particles only, while the estimation of j gas made use of all gas particles that have a neutral gas fraction > 0. Lagos et al showed that the stellar M *j * relation in EAGLE galaxies of different morphologies has good agreement with measurements in the local universe by Romanowsky & Fall (2012); Obreschkow & Glazebrook (2014); Cortese et al (2016). The resolution limit of the simulation constrains the galaxy selection.…”
Section: Calculation Of the Q Parametermentioning
confidence: 89%
“…To estimate j * , they used star particles only, while the estimation of j gas made use of all gas particles that have a neutral gas fraction > 0. Lagos et al showed that the stellar M *j * relation in EAGLE galaxies of different morphologies has good agreement with measurements in the local universe by Romanowsky & Fall (2012); Obreschkow & Glazebrook (2014); Cortese et al (2016). The resolution limit of the simulation constrains the galaxy selection.…”
Section: Calculation Of the Q Parametermentioning
confidence: 89%
“…We show the relation between ∆j and Sérsic index for z ∼ 0 galaxies from Romanowsky & Fall (2012). The parameterisation of the relation is taken from Cortese et al (2016) who established the j * -M *n relation for the SAMI survey. We note the parameterisation derived in Cortese et al (2016) is for a morphologically diverse population of both quiescent and star-forming low redshift galaxies, and therefore should not be compared directly to our sample of star-forming selected high-redshift galaxies.…”
Section: Quantised Morphology and Dynamicsmentioning
confidence: 99%
“…More recent integral field studies of low redshift galaxies have analysed the connection between a galaxy's parameterised morphology (e.g. Sérsic index, stellar bulge to total ratio) and specific angular momentum (Obreschkow & Glazebrook 2014;Cortese et al 2016). More bulge dominated galaxies, with higher Sérsic indices, have been shown to have lower specific angular momentum at fixed stellar mass (Fall & Romanowsky 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A galaxy's accretion and merger history is central to defining its character, and aspects of this history are encoded in the lineof-sight velocity distributions. By studying the detailed kinematics of galaxies across the mass and environment plane, we unlock a new view of galaxy evolution (Cortese et al 2016;van de Sande et al 2017). IFS has defined a new set of morphological classifications in terms of dynamical properties (e.g.…”
Section: Hill 2014mentioning
confidence: 99%